Pathways to illness, pathways to health - McGrady, Angele; Moss, Donald (Springer New York Imprint: Springer, 2013)
Why is this person healthy when that one is ill? The trained provider is well schooled in the roles of genetics, environment, lifestyle choices, and pure luck in individuals' well-being. But now a groundbreaking new book clearly identifies the turning points that lead from wellness to disease--and how patients can be re-routed back to health. Pathways to Illness, Pathways to Health is no simple metaphor but a powerful model for healing that views health and disease along a continuum, with patient and provider as partners on the journey. A rigorous evidence base pinpoints causal variables for illness (particularly stress-related disorders) that can be targets for change, and is the basis for recommended healthful behaviors and restorative therapies. Case histories illustrate a detailed ongoing assessment process and three progressive levels of intervention chosen from a variety of techniques and modalities, ranging from biofeedback and mindful breathing to cognitive-behavioral therapy and acceptance and commitment therapy. Included in the coverage:  Genetic and psychosocial etiologies of illness. Psychophysiological aspects of stress. Guidelines for comprehensive assessment. The conceptual framework: interventions in the pathways model. Applications to common illnesses: diabetes, obesity, substance abuse, depression, anxiety, cardiovascular disease, back pain, sleep disorders, fibromyalgia, and more. Personalizing the path to health and wellness. Health psychologists, clinical psychologists, primary care physicians, nurses, medical students and residents, and practitioners in holistic health and in alternative and complementary medicine will find in Pathways to Illness, Pathways to Health a clear set of signposts leading to the future of care.